Ecosystem resistance in the face of climate change: a case study from the freshwater marshes of the Florida Everglades. Issue 4 (17th April 2015) - Malone, Sparkle L.; Keough, Cynthia; Staudhammer, Christina L.; Ryan, Michael G.; Parton, William J.; Olivas, Paulo; Oberbauer, Steven F.; Schedlbauer, Jessica; Starr, Gregory
Abstract : Shaped by the hydrology of the Kissimmee‐Okeechobee‐Everglades watershed, the Florida Everglades is composed of a conglomerate of wetland ecosystems that have varying capacities to sequester and store carbon. Hydrology, which is a product of the region's precipitation and temperature patterns combined with water management policy, drives community composition and productivity. As shifts in both precipitation and air temperature are expected over the next 100 years as a consequence of climate change, CO2 dynamics in the greater Everglades are expected to change. To reduce uncertainties associated with climate change and to explore how projected changes in atmospheric CO2 concentration and climate can alter current CO2 exchange rates in Everglades freshwater marsh ecosystems, we simulated fluxes of carbon among the atmosphere, vegetation, and soil using the DAYCENT model. We explored the effects of low, moderate, and high scenarios for atmospheric CO2 (550, 850, and 950 ppm), mean annual air temperature (+1, +2.5, and +4.2°C) and precipitation (−2, +7, and +14%), as predicted by the IPCC for the year 2100 for the region, on CO2 exchange rates in short‐ and long‐hydroperiod wetland ecosystems. Under 100 years of current climate and atmospheric CO2 concentration, Everglades freshwater marsh ecosystems were estimated to be CO2 ‐neutral. As atmospheric CO2 concentration increased and under climate change projections, there were slight shifts in the start and length of the wet season (−1 to +7 days) and a small enhancement in the sink capacity (by −169 to −573 g C m −2 century −1 ) occurred at both short‐ and long‐ hydroperiod ecosystems compared to CO2 dynamics under the current climate regime. Over 100 years, rising temperatures increased net CO2 exchange rates (+1 to 13 g C m −2 century −1 ) and shifts in precipitation patterns altered cumulative net carbon uptake by +13 to −46 g C m −2 century −1 . While changes in ecosystem structure, species composition, and disturbance regimes were beyond the scope of this research, results do indicate that climate change will produce small changes in CO2 dynamics in Everglades freshwater marsh ecosystems and suggest that the hydrologic regime and oligotrophic conditions of Everglades freshwater marshes lowers the ecosystem sensitivity to climate change.